Microbial community diversity from nearshore to offshore in the East China Sea - Jin, Jian; Liu, Xiujie; Zhao, Wenbin; Sun, Hao; Tan, Siyin; Zhang, Xiao-Hua; Zhang, Yunhui (Frontiers in Microbiology, 2024)
The Pollution Nagasaki (PN) section of the East China Sea (ECS) is a typical area for studying the complex hydrographic dynamics between Changjiang River discharge and Kuroshio, displaying intense variations of environmental gradients from nearshore to offshore. However, the temporal and spatial changes of microbial communities along the PN section have long been overlooked. In this study, we performed a comprehensive investigation into the abundance, diversity and ecology of free-living (FL) and particle-associated (PA) microbial communities in seawater samples along the PN section during both summer and winter. Distinct hydrological conditions and resulting environmental gradients were observed between summer and winter, with clear features of intrusive Kuroshio subsurface water in summer and strong vertical mixing of seawater in winter. Bacterial abundance along the PN section was higher in summer (1.11 × 108 copies·L−1 – 7.37 × 108 copies·L−1) than in winter (1.83 × 106 copies·L−1 – 1.34 × 108 copies·L−1). Microbial diversity, as indicated by α-diversity indices, remained at relatively stable levels in summer, while a clear decreasing trend was observed in winter along the PN section. Additionally, the winter communities exhibited a more evident spatial shift along the PN section compared to the summer communities. 16S rRNA gene amplicon sequencing showed that microbial community composition varied considerably between different seasons (summer and winter) and lifestyles (FL and PA), with a notable dominance of Ralstonia species. in winter. Regarding the assembly of microbial communities, the stochastic process represented by dispersal limitation was the dominant process in summer, while the deterministic homogeneous selection was the most important process in winter. Correspondingly, distinct topological properties of the microbial co-occurrence networks were shown between different seasons and along the PN section. These results enhance our understanding of how hydrological conditions influence dynamic changes of microbial communities along the PN section, providing new insights for the microbial community assembly and interactions in such a complex environment.